Observations and Predictions of Arctic Climatic Change: Potential Effects on Marine Mammals - Tynan, Cynthia T.; DeMaster, Douglas P. (ARCTIC, 1997)
Recent analyses have revealed trends over the past 20-30 years of decreasing sea ice extent in the Arctic Ocean coincident with warming trends. Such trends may be indicative of the polar amplifications of warming predicted for the next several decades in response to increasing atmospheric CO2. We have summarized these predictions and nonuniform patterns of arctic climate change in order to address their potential effects on marine mammals. Since recent trends in sea ice extent are nonuniform, the direct and indirect effects on marine mammals are expected to vary geographically. Changes in the extent and concentration of sea ice may alter the seasonal distributions, geographic ranges, patterns of migration, nutritional status, reproductive success, and ultimately the abundance and stock structure of some species. Ice-associated seals, which rely on suitable ice substrate for resting, pupping, and molting, may be especially vulnerable to such changes. As recent decreases in ice coverage have been more extensive in the Siberian Arctic (60 E-180 E) than in the Beaufort Sea and western sectors, we speculate that marine mammal populations in the Siberian Arctic may be among the first to experience climate-induced geographic shifts or altered reproductive capacity due to persistent changes in ice extent. Alteration in the extent and productivity of ice-edge systems may affect the density and distribution of important ice-associated prey of marine mammals, such as arctic cod, Boreogadus saida, and sympagic ("with ice") amphipods. Present climate models, however, are insufficient to predict regional ice dynamics, winds, mesoscale features, and mechanisms of nutrient resupply, which must be known to predict productivity and trophic response. Therefore, it is critical that mesoscale process-oriented studies identify the biophysical coupling required to maintain suitable prey availability and ice-associated habitat for marine mammals on regional arctic scales. Only an integrated ecosystems approach can address the ...